A novel multicriteria sustainability investigation of energy storage systems. (6th March 2019) - Acar, Canan; Beskese, Ahmet; Temur, Gül Tekin
Summary: Affordable, clean, efficient, flexible, and reliable energy storage is an important component of sustainable energy systems. There are several studies in the literature concentrating on improving the sustainability performance of energy storage systems from economic and technical perspectives. However, a comprehensive performance investigation of energy storage systems that take economic, environmental, social, and technical criteria into account is still needed. For that reason, in the present study, it is aimed to perform a complete assessment and analysis of the sustainability of energy storage systems for residential applications in communities and cities. Pumped hydro, conventional batteries, high‐temperature batteries, flow batteries, and hydrogen are the selected energy storage systems. In order to handle the vagueness and ambiguity during the assessment and to eliminate the perceived hesitancy in the decision makers' preferences, an innovative method, a hybrid hesitant fuzzy multicriteria decision‐making (MCDM) methodology composed of hesitant fuzzy analytic hierarchy process (HFAHP) and hesitant fuzzy technique for order preference by similarity to ideal solution (HFTOPSIS), is utilized to assess the sustainability of the selected systems. In this study, four different performance criteria: economic (power cost and energy cost), environmental (pollutant emissions, area requirement, wastewater quality, and solid waste production), social (safety, accessibility, ease of use, and public acceptance), and technical (efficiency, storage capacity, cycling limit, and performance degradation) are taken into consideration. The performance evaluation results indicate that technical performance has the highest influence and social performance has the lowest influence when evaluating the sustainability of the selected energy storage systems. And hydrogen has the highest sustainability performance compared with the other selected energy storage options. Abstract : In the literature, there is a growing need for a comprehensive economic, environmental, social, and technical assessment of energy storage systems. For that reason, the most important objective of this study is to conduct a complete sustainability performance investigation of energy storage systems. Overall, this study is one of the first approaches in the literature on evaluating the sustainability of energy storage systems from a broader perspective by taking social, technical, environmental, and economic criteria into account at once.